FINANCIAL ROBO-ADVISOR SAVINGS2U FOR SHARIAH-COMPLIANT SAVINGS AND INVESTMENT APPLICATION - Mohammad Firdaus Mohammad Hatta; Nur Diniey Ezzati Zainorin; Syuhada Jalaludin; Norzanah Mat Nor; Suriana Ramli (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The growing usage of artificial intelligence such as Robo-Advisor has become one of the biggest developments in the global economy and reduces the level of poverty in the country with a safe, affordable and frictionless environment. In practice, Malaysians have low awareness and not financial discipline about personal savings and financial management. Most of Malaysian people have problems with their retirement planning because they really rely on their EPF funds as their primary source of income. The purpose of this product is to create awareness about the importance of savings and investment for all generations, reduce future financial issues faced by consumers, and encourage people to build wealth based on customer preference. As a result, customers will be more likely to develop a good habit of saving their money for the future and achieving their financial goals. This study used quantitative and secondary data which is collected from The World Bank website. We develop an application of financial Robo-Advisor known as Savings2u that focus on savings and Shariah compliance investment features based on customer risk preference such as conservative or aggressive then let the money grow digitally. In conclusion, Savings2u will help the customer to create and manage the portfolio automatically using the data provided. On the other hand, an increase in total savings would have a beneficial effect on the economic growth, which includes significant investments and an improvement in GDP of the country. Furthermore, countries with deeper and established financial systems also experienced stronger economic growth.